2022
DOI: 10.1093/mnras/stac2421
|View full text |Cite
|
Sign up to set email alerts
|

UOCS –VIII. UV study of the open cluster NGC 2506 using ASTROSAT

Abstract: We study an intermediate-age open cluster NGC 2506 using the ASTROSAT/UVIT data and other archival data. We identified 2175 cluster members using a machine learning-based algorithm, ML–MOC, on Gaia EDR3 data. Among the cluster members detected in UVIT filters, F148W, F154W, and F169M, we detect 9 blue straggler stars (BSS), 3 yellow straggler stars (YSS) and 3 red clump (RC) stars. We construct multi-wavelength spectral energy distributions (SEDs) of these objects to characterize them and to estimate their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 122 publications
1
5
0
Order By: Relevance
“…M 67 has been found to be home to multiple extremely low-mass (ELM) WDs, which are products of mass transfer (Sindhu et al 2019;Jadhav et al 2019;Subramaniam et al 2020;Pandey et al 2021;Vernekar et al 2023). Similar mass-transfer binaries have been found in NGC 7789 (Vaidya et al 2022) and NGC 2506 (Panthi et al 2022). Here, we extend this study to the open cluster NGC 6791 (α 2000 = 19h20m53s; δ 2000 = +37 • 46 18 ; l = 69.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…M 67 has been found to be home to multiple extremely low-mass (ELM) WDs, which are products of mass transfer (Sindhu et al 2019;Jadhav et al 2019;Subramaniam et al 2020;Pandey et al 2021;Vernekar et al 2023). Similar mass-transfer binaries have been found in NGC 7789 (Vaidya et al 2022) and NGC 2506 (Panthi et al 2022). Here, we extend this study to the open cluster NGC 6791 (α 2000 = 19h20m53s; δ 2000 = +37 • 46 18 ; l = 69.…”
Section: Introductionsupporting
confidence: 69%
“…The UV excess has been linked to the presence of hot compact objects such as WDs (Jadhav et al 2019;Rao et al 2022;Panthi et al 2022) or hot subdwarfs . One can use double-component SED fitting to deconvolve the two stars.…”
Section: Spectral Energy Distributionsmentioning
confidence: 99%
“…It has been revealed through spectroscopic and UV observations that in many OCs, such as NGC 188 (Geller et al 2008;Gosnell et al 2015), M67 (Geller et al 2015;Sindhu et al 2019;Jadhav et al 2019), NGC 6819 (Milliman et al 2015, and NGC 7789 (Nine et al 2020;Vaidya et al 2022), ∼33% -85% of BSS formed via binary system evolution, primarily through the mass-transfer channel. The triple-mediated interactions are also considered as an important formation channel for some BSS of OCs, such as M67 and NGC 188 (Leigh & Sills 2011;Leiner et al 2016;Bertelli Motta et al 2018), Melotte 66 (Rao et al 2022), and NGC 2506 (Panthi et al 2022). Furthermore, Ferraro et al (2009) and Dalessandro et al (2013) found that blue sequences of M30 and NGC 1261 contain W UMa binaries.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature range of BSSs in OC M67 (4 Gyr) is 6250 −9000 K (Jadhav et al 2019), in King 2 (6 Gyr) it is 5750-8500 K , and in OC NGC 188 (7 Gyr) it is 6100−6800 K (Gosnell et al 2015). In intermediate-age OCs such as NGC 7789 (1.6 Gyr) (Vaidya et al 2022) and NGC 2506 (2.2 Gyr) (Panthi et al 2022), BSSs span a temperature range from 7250 to 10,250 K, and 7750−9750 K, respectively. The SEDs of all BSSs are well-fitted with a single model, and we suggest that collisions leading to mergers might explain their formation in this cluster.…”
Section: Discussionmentioning
confidence: 99%